Response to Thalamic Ventralis Intermedius Nucleus Deep Brain Stimulation in Essential Tremor vs. Essential Tremor-Plus - Gilmour, Gabriela S.; Martino, Davide; Hunka, Karen; Lawrence, Pia; Kiss, Zelma H. T.; Bruno, Veronica (Frontiers in Neurology, 2021)
Introduction Essential tremor (ET) is a tremor syndrome characterized by bilateral, upper limb action tremor. Essential tremor-plus (ET-plus) describes ET patients with additional neurologic signs. It is unknown whether there is a difference in response to treatment with ventralis intermedius nucleus deep brain stimulation (VIM DBS) in patients with ET and ET-plus. Due to potential variability in underlying etiology in ET-plus, there is a concern that ET-plus patients may have worse outcomes. The aim of this study was to identify whether patients with ET-plus have worse tremor outcomes after VIM DBS than patients with ET. Methods This is a retrospective chart and video review evaluating VIM DBS outcomes by comparing changes from baseline in the Fahn-Tolosa-Marin Tremor Rating Scale Part B (FTM-B) for the treated limb between patients with ET and ET-plus at follow-up examinations. Patients were re-classified as having ET or ET-plus using pre-operative examination videos by two independent movement disorders neurologists blinded to patient characteristics. As a secondary outcome, we evaluated for correlations and potential predictors of treatment response. Results Twenty-six patients were included: 13 with ET, 13 with ET-plus. There were no significant differences in the change in FTM-B scores between the ET and ET-plus patients at each follow-up examination. None of the included patients developed new symptoms compatible with dystonia, parkinsonism or gait disturbances. Conclusions Patients with ET-plus had tremor improvement from VIM DBS, with no differences when compared to those with ET, without emergence of postoperative neurological issues. Patients with ET-plus should still be considered good candidates for VIM DBS for treatment of tremor.